Effect of incorporated hybrid MIL-53(Al) and MWCNT into PES membrane for CO2/CH4 and CO2/N2 separation - Saeid Rostami, Mohammad; Mehdi Khodaei, Mohammad (Fuel (Guildford), 2024)
MIL-53(Al) particles and –COOH functionalized multiwalled carbon nanotube (MWCNT-COOH) were combined as the dispersed phase to synthesize a hybrid structure, MIL-53(Al)@MWCNT. In the next step, MIL-53(Al)@MWCNT was embedded in a polyethersulfone (PES) polymer matrix to prepare PES/MIL-53(Al)@MWCNT mixed matrix membrane (MMM) for CO2 separation from CH4 and N2. [Display omitted] •Fabrication of the new mixed-matrix membranes (MMMs) with PES, MIL-53(Al), and MWCNTs.•The fabricated MMMs showed higher CO2 permeability along with CO2/CH4 and CO2/N2 selectivity than pure membrane.•MMMs showed CO2 permeability increases with increasing loadings.•MMMs showed improved thermal and mechanical properties.•The affinity of –COOH group on CO2 molecules in MWCNT. In this study, MIL-53(Al) particles and –COOH functionalized multi-walled carbon nanotube (MWCNT) were combined as the dispersed phase to synthesize a hybrid structure, MIL-53(Al)@MWCNT. In the next step, MIL-53(Al)@MWCNT was embedded in a polyethersulfone (PES) polymer matrix to prepare PES/MIL-53(Al)@MWCNT mixed matrix membrane (MMM) for CO2/CH4 and CO2/N2 separation. Different techniques, including SEM, XRD, FT-IR, BET, and TGA, were used to confirm the successful synthesis of MMMs. Adding MWCNTs prevented MIL-53(Al) aggregation in the polymer matrix and enhanced membrane mechanical properties and gas separation efficiency. Furthermore, the correlation between MWCNT and MIL-53(Al) created a rapid transfer channel for CO2 molecules. According to the results, the MMM containing 5 wt% of MIL-53(Al)@MWCNT showed high CO2/N2 and CO2/CH4 ideal selectivity of 87 and 58.6 along with a desired permeability of 183 barrer than the pure PES membrane indicating a favorable CO2 separation efficiency. Moreover, performance shifted towards the corresponding upper bounds.